Design and development of a NLP demo system - Ong, Yi Xiong (Nanyang Technological University, 2022)
Natural language processing (NLP) is used to enable machines to understand and derive meaning from human language data. NLP has many applications such as predictive text, and sentiment analysis which signifies NLP as a field of interest. NLP is hence offered as a key subject in many educational institutions. To enhance teaching and learning experiences, the main objective of this project is to develop an interactive platform that is able to depict the results of different NLP libraries on different NLP techniques in a standardized visual format. The intended purpose of the project is to provide an one-stop platform with an easy-to-use interface to NLP libraries and techniques that educators and students alike could use to facilitate the teaching and learning of NLP concepts. The report entails the introduction of the project and the proposed NLP demo web application. It also entails the requirements for the web application and the technology stack adopted. Implementation details of the components are included, followed by possible future work and conclusion.